Du papillon à la chrysalide ou l’étrange métamorphose de l’assurance de responsabilité - Faribault, Bernard (Assurances, 1987)
Article 2603 of the Civil Code states that an injured third party may directly sue a tortfeasor's insurer. A few authors and one judgment have interpreted this article to mean that an insurer may not set up a denial of coverage against injured third parties for breach of contract which occurred after the loss and which he could set up as a defence against the assured's claim. Me Faribault looks at this aspect of the question and suggests that such an interpretation may well lead to the tail wagging the dog.